A STUDY OF THE EFFECT OF SALINITY AND PH ON BIOFILM FORMATION OF HALOARCHAEA ISOLATED FROM LAKE KOBEITUZ - Khani, Ainur (Nazarbayev University School of Sciences and Humanities, 2024)
Haloarchaea are microorganisms that thrive best in extremely salty environments. Some studies suggest that some genera of Haloarchaea are capable of forming biofilms. Although the biofilm formation process of archaea resembles a process of bacterial biofilms, the precise mechanism of this process remains poorly understood, especially concerning the impact of environmental conditions. The objective of this study was to examine the effects of varying concentrations of MgCl2, as well as changes in pH, on the formation of biofilms by Haloarchaea that have been isolated from Lake Kobeituz. The biofilms were examined using indirect quantitative (microtiter dish assay) and direct examination with a brightfield microscope. Our study postulated that salinity and pH variations had a major impact on haloarchaea biofilm formation, thereby opening a basis for modulation and a better understanding of the process. During our study, it was revealed that Haloarchaea’s response to stress and biofilm formation is species-specific. All three Haloarchaeal isolates differed in strength of surface attachment, biofilm morphology, and biofilm production. The strongest biofilm producer was Halobacterium salinarum, which demonstrated the highest biofilm growth at pH 7 and 100 mM MgCl2. Although we identified favorable conditions for haloarchaea growth, further proteomic studies should be conducted to fill the gaps in the stress response and metabolism of Haloarchaea.
Keywords: Type of access: Restricted; Haloarchaea; Kobeituz; biofilms